Educational AI technologies: from useful to problematic - Зайда А. В. (2024, 2024)
This paper identifies and explores newly popular AI technologies that have found use in education and academia. AI tools were categorized by their potential usefulness for education. Specifically, AI detection tools were analyzed more closely. Conducted experiment suggested that the accuracy of such tools varies a lot and is often insufficient to be used in judgment of text authenticity